Resection of the Tooth Apex with Diode Laser - Uzunov Tz. (Sciendo, 2014)
An “in vitro” experimental study has been carried out on 70 extracted teeth. A laser resection of the root apex has been carried out with diode laser beam with a wavelength of - 810 ± 10 nm. Sequentially a radiation with increasing power has been applied, as follows: 1,3 W, 2W, 3W, 4W, 5W, 6W, 7W, in electro surgery mode. Successful resection of the tooth apex has been performed at: 3W; 4W; 5W; 6W and 7W power. It was established that when laser resected the tooth apex carbonizes.